Part A : 30 - x - x - x - x - x - x = 0
^ since 30 divided by 5 is 6, that answer is the same as doing 5 + 5 + 5 + 5 + 5 + 5
- pls comment & correct me if i did smth wrong :’)
Answer:
I would help but I am not good with graphing.
The answer is B). graph B
Answer:
Substitution property of equality
Step-by-step explanation:
Given
and 
Then

Required
State the property
From the list of options, (d) answers the question.
This is so because:
Substitution property of equality states that
If
then 
In other words, both can replace one another.
So if
, then 2y + 1 can be substituted for x in
So:
becomes

<em>Hence, it is substitution property of equality</em>
Answer:
2
Step-by-step explanation:
What you could do is fill in 2 for the equation and y would equal -3 so for the first one it's like
y= 2^2 + 5(2) -17
y= 4 + 10 - 17 which turns into y= -3
In the second y it would be something like
y= 2 - 5 which would equal y= -3
so x=2